SMED applied to composed cork stoppers - Sousa, Eduardo (2019)
A growing focus among organizations is their flexibility in production. The market pressure for products with large variety in small batches leads organizations to maximize their resources in order to be able to adapt their processes to constant changes. One of the most known barriers in processes flexibility is the equipment changeover time. To reduce this time and thus increase the processes flexibility and the organization competitiveness in the market, the Lean methodology can be applied, being Single Minute of Exchange of Die (SMED) methodology the most used Lean tool in this context. This chapter intends to present a practical case with mixed Lean tools application, being mainly focused on SMED study and implementation in cork industry equipment, leading to reduce the changeover time. There are several publications about SMED application in the most varied industrial areas, being this work an innovation in the cork industry. The equipment under study performs the connection between cork stoppers to capsules, which is done by glueing them with hot-melt glue. In order to start this kind of studies, it is important to know the initial equipment condition and for this the equipment data need to be initially collected. With these data, it is possible to identify the improvement opportunities. In order to recognize which activities really add value to the product, the Value Stream Mapping (VSM) technique is usually used. The SMED is applied as a mean to reduce the downtime caused by changeover activities. To follow the development of the SMED project, another valuable lean tool is the A3 report. Lastly, in a way to improve the monitoring of possible deviations during production, the Overall Equipment Efficiency (OEE) KPI can be implemented as an overall equipment efficiency indicator. The aforementioned lean tools were successfully applied in the composed cork stopper manufacturing process, resulting in a 43% changeover time decrease from 66:56 min to 37:59 min through the application of SMED and, at the end of this study it is possible to prove that lean tools and principles are a powerful approach to get solid profits without large investments, as well as their important contribution to increase the processes flexibility.